The Role of Voluntary Accounting Disclosure in Measuring the Cost of Financing Sources: An Applied Study on a Sample of Commercial Banks Listed on the Iraq Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to study the relationship and impact between voluntary accounting disclosure and banking financing sources, with a focus on its role in enhancing transparency and its reflection on stakeholders, particularly in reducing financing costs and improving the reliability of financial reports. The study adopts a quantitative approach, employing statistical methods to analyze the relationship between its variables. The research population consists of Iraqi banks, with a sample of ten banks listed on the Iraq Stock Exchange for the period (2019–2023). Various statistical techniques were applied to assess the relationship between voluntary accounting disclosure and banking financing sources, as well as its impact on financial stakeholders' decisions. The study also relies on the deductive approach for theoretical studies and variable interpretation.The findings indicate that voluntary accounting disclosure provides significant benefits, offering a clear insight into a bank’s strategy and its ability to maximize its value, which contributes to lowering financing costs. The results also show that presenting both financial and non-financial data, along with performance indicators and future projections, enhances decision-making and mitigates the issue of information asymmetry. Based on these findings, the study recommends enhancing the level of voluntary accounting disclosure in Iraqi banks and organizing seminars in collaboration with professional and academic entities to raise awareness. It also emphasizes the role of regulatory bodies in ensuring the accuracy and transparency of financial reports, as well as educating investors and lenders about the importance of investing in banks that adhere to high disclosure standards. Finally, the research advocates for the adoption of international accounting standards to strengthen confidence in financial statements and reduce financing costs.